Patterns And Determinants Of Caesarean Section Rates According To Modified Robsons Criteria: A Descriptive Study From A Tertiary Care Hospital - Qureshi, Fozia Umber; Sohail, Shaherzad; Jabeen, Saima; Iqbal, Faiza (Journal of Rawalpindi Medical College, 2025)
Objective: The underlying purpose of this clinical audit is to categorize cesarean sections according to maternal characteristics as described in Modified Robson’s Criteria, which facilitates the identification of the major contributing factors to the rapidly rising rate of cesarean sections (CS). Materials and Methods: This retrospective study was conducted at Shalamar Hospital, Lahore, Pakistan. It is a descriptive analysis based on the delivery records of 3,925 women who delivered in the obstetric units of Shalamar Teaching Hospital from October 1st, 2022, to September 30th, 2023. Data collection was done using a research questionnaire which recorded data for relevant maternal characteristics. Then, the data was classified per Robson’s criteria. The resultant involvement of each group was calculated to monitor each group’s share in the consequent CS rate. Lastly, sorting data observations for noting the frequency of cesarean indications was included in the study to deliver eloquent discernments. Non-reassuring CTG and failed induction of labor were found to be the most prominent indications for cesarean deliveries. Results: Out of the 3925 deliveries recorded, 2886 (73.5%) were cesarean sections. According to the criterion used, the major contributor to the overall Cesarean Section rate was Group 5, which includes previous cesarean delivery, single, cephalic, ≥37 weeks, accounting for almost 50% of the cesarean deliveries. The second largest group was Group 2 (22.1%), followed by Group 1 (9.3%), which heightens the overall CS rates. An enhanced level of medical intervention during pregnancy and low preferences of vaginal birth shift maternal as well as obstetric preferences towards cesarean sections which needs to be addressed. Conclusion: Modified Robson’s criteria is an effective tool for auditing cesarean sections to identify exact areas where efforts and strategies are required to reduce the overall CS rate. Women with previous 1 scar should be assessed and offered a trial of labor after cesarean section, where appropriate. Groups 1, 2 and 5 should be subjected to necessary intervention to curb the rising CS rates and support VBAC.